Potensi Daun Afrika (Vernonia amygdalina) sebagai Antidiabetik - Yunisa Arini Putri (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Diabetes mellitus can be defined as a disease or chronic metabolic disorder characterized by high blood sugar levels accompanied by impaired carbohydrate, lipid, and protein metabolism as a result of insulin function insufficiency. In 2017, people with diabetes mellitus reached 425 million or 8.8% of adults in the age range of 20-79 years people worldwide and every 8 seconds one person died of diabetes mellitus. Numerous studies show that African leaves or Vernonia amygdalina can be antidiabetic drugs. Phytochemicals that can be found in African leaves are flavonoids, alkaloids, tannins, saponins, glycosides, terpenoids, glycosides and reducing sugars which play a role in inhibiting gluconeogenesis and increasing insulin sensitivity.